On the Constitutive Force of Regulative Rules - Wojciech Zełaniec (Rosenberg & Sellier, 2016)
The paper deals with the problem of delimitation of regulative and constitutive rules. I argue that while regulative rules are and remain a genus of their own, they do have a constitutive import, because they (i) define new forms of behaviour (behaviour compliant with them), (ii) take constituted entities as “input”, (iii) redefine old forms of behaviour as such to which a deontic modality applies and (iv) help to carve out new possibilities of behaviour from a continuum of only potentially distinguishable possibilities.